Improving Employee Performance Through Ability and Career Development - Adiwinata, Djaka; Marlisa, Serli; Azizi, Enji (Fakultas Ekonomi, Universitas Negeri Jakarta, 2025)
This study aims to examine the influence of ability and career development on employee performance at PT Buana Berlian Indonesia. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 44 employees. The data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Square (PLS). The results indicate that both ability and career development, either partially or simultaneously, have a positive and significant effect on employee performance. These findings highlight the importance of enhancing employee abilities and implementing structured career development plans to improve performance sustainably. Therefore, it is recommended that the company provide training and career development programs to enhance work effectiveness and employee motivation..